Influential factors in the surface-hardness testing of a nitrided layer - Cajner, Franjo (Materiali in tehnologije, 2013)
Nitrocarburizing is one of the frequently applied processes that significantly improve the service life of steel parts in the complex activities of mechanical loads, wear and corrosion damages. Characterization and confirmation of the quality of a nitrided/nitrocarburized layer is a prescribed norm including a determination of the surface hardness, nitriding hardening depth, compound-zone thickness and its porosity. In the testing of the surface hardness, in spite of determined conditions, there are additional factors that can affect the obtained result and can lead to a misunderstanding between a customer and a provider of the service of nitriding. In this paper, possible influential factors related to the surface hardness are considered and statistically analyzed by the ANOVA two-factor test. The considered influential factors are: the surface-preparation method and the loading force. The tests carried out during the research indicated a significant influence of the loading force and of the surface preparation on the results of the nitrided/nitrocarburized-steel surface hardness. Also, the indentation size effect is confirmed in the hardness tests with a small loading force.
Keywords: nitriding/carburizing; nitriranje; nitrocementiranje; surface hardness; trdota površine